Hubungan Penggunaan Rokok Elektrik dengan Status Kebersihan Gigi dan Mulut pada Komunitas Manado Vapers - Oroh, Junior N.W.; Suling, Pieter L.; Zuliari, Kustina (Universitas Sam Ratulangi, 2018)
Abstract: E-cigarette or electronic cigarette is one of the methods of nicotine replacement therapy (NRT) designed to replace nicotine intake without tobacco. Initially, it was thought that the e-cigarette was a much safer alternative than the conventional cigarette. In fact, this e-cigarette can still pose dangerous side-effects to the usersâ€™ general health, including oral and dental health. This study was aimed to identify the relationship between the frequency of e-cigarette use and dental and oral health status in a community called Manado vapers in Manado. Samples were 32 e-cigarette users obtained by using total sampling of the community that fulfilled the inclusion criteria of this study. This was a descriptive analytical study with a cross-sectional design. Data were obtained by using questionnaire and OHI-S index. The Pearsonâ€™s correlation test performed on the relationship between the frequency of e-cigarette and oral health as well as dental health obtained a P value of 0.556. Conclusion: There was no significant relationship between frequency of e-cigarette use and oral and dental health among Manado vapers community in Manado.Keywords: smoking, e-cigarette, oral and dental health statusÂ Abstrak: Rokok elektrik merupakan salah satu nicotine replacement therapy (NRT) yang dirancang untuk memberikan asupan nikotin tanpa pembakaran tembakau. Cara ini dikatakan lebih aman daripada rokok konvensional, namun ternyata tetap terdapat dampak bagi kesehatan tubuh, termasuk juga kesehatan gigi dan mulut. Penelitian ini bertujuan untuk mengetahui hubungan frekuensi penggunaan rokok elektrik dengan status kebersihan gigi dan mulut pada komunitas Manado vapers di kota Manado. Sampel penelitian ini yaitu 32 responden yang merupakan anggota Manado vapers pengguna rokok elektrik diambil menggunakan metode total sampling. Jenis penelitian ialah deskriptif analitik dengan desain potong lintang. Data diperoleh dengan menggunakan kuesioner dan indeks OHI-S. Hasil uji korelasi Pearson terhadap hubungan antara frekuensi penggunaan rokok elektrik dengan status kebersihan gigi dan mulut mendapatkan nilai P = 0,556. Simpulan: Tidak terdapat hubungan bermakna antara frekuensi penggunaan rokok elektrik dengan status kebersihan gigi dan mulut pada komunitas Manado vapers di kota Manado.Kata kunci: merokok, rokok elektrik, status kesehatan gigi dan mulut